2021
DOI: 10.1371/journal.pone.0252880
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the nomophobic levels of higher education students in Ghana and academic achievement

Abstract: There is an upsurge in the use of mobile phones among higher education students in Ghana, which may result in the nomophobia prevalence with the students. Therefore, the need to assess the influence of nomophobia within the student population in Ghana. This descriptive cross-sectional study investigated the prevalence of nomophobia and the sociodemographic variables, and the association with academic achievement of the understudied population. A self-reporting nomophobia questionnaire, composed of 20 dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 62 publications
3
17
1
Order By: Relevance
“…t (441) = 1.004; p = 0.316). This result is in line with results similar to Essel et al (2021). However, the results were different from the research by Le on-Mejía et al (2021), who showed that young women would suffer more from the effect of nomophobia.…”
Section: Analysis Of Meanssupporting
confidence: 84%
See 4 more Smart Citations
“…t (441) = 1.004; p = 0.316). This result is in line with results similar to Essel et al (2021). However, the results were different from the research by Le on-Mejía et al (2021), who showed that young women would suffer more from the effect of nomophobia.…”
Section: Analysis Of Meanssupporting
confidence: 84%
“…However, it is essential to consider other effects that affect mental health for future studies. The survey results support the need for further research on the effects of nomophobia in specific problematic environments, such as the cyberloafing effect (Chatterjee, 2020;Essel et al, 2021;Kara et al, 2019;Masadeh, 2021).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations